Sistem Informasi Publik Dan Aspirasi Masyarakat Berbasis Web Pada Pemerintah Desa Kalikuto Kecamatan Grabag - Atun Ariyanto; Kapti; Fatkhurrochman (LPPM Universitas An Nuur, 2026)
The purpose of this research is to design and build a web-based public information and community aspiration system at the Government of Kalikuto Village as well as to determine the impact of the implementation of the web-based public information and community aspiration system at the Government of Kalikuto Village. The research method used is a software engineering approach with the Waterfall system development model. The data collection methods used are observation, interviews, and documentation. The problem analysis method used is PIECES. The design used in this research is UML (Unified Modeling Language) with the PHP programming language and MySQL database using the CodeIgniter framework. The result of this research is the successful design and development of a web-based public information and aspiration system for the Kalikuto Village Government. System testing using Black Box Testing obtained a 100% conformity rate for all system functions. This study also successfully identified the impact of the system implementation, as demonstrated by the user evaluation results through a questionnaire using the Likert Scale. The feasibility score was 85.4%, indicating that the system is highly feasible for implementation. With the existence of this public information and aspiration system, it is expected to improve service activities in Kalikuto Village.